Effect of Quiet and Noise on P300 Response in Individuals with Auditory Neuropathy Spectrum Disorder - Apeksha,Kumari (2020)
Abstract Introduction Auditory neuropathy spectrum disorder (ANSD) is a clinical condition in which individuals have normal cochlear responses and abnormal neural responses. There is a lack of evidence in the literature regarding the neural discrimination skill in individuals with ANSD, especially when the signal is presented in the presence of noise. Objectives The present study was performed with the aim to investigate auditory discrimination skill, in quiet and in the presence of noise, in individuals with ANSD and to compare the findings with normal-hearing individuals. Methods A total of 30 individuals with normal hearing sensitivity and 30 individuals with ANSD in the age range of 15 to 55 years old, with the mean age of 27.86 years old, were the participants. P300 response was recorded from both groups using syllable pairs /ba/-/da/ in oddball paradigm and the syllable /da/ in repetitive paradigm in quiet and at +10 dB signal-to-noise ratio (SNR). Results There was significant prolongation in latency and reaction time, and reduction in amplitude of P300 response and sensitivity in both groups with the addition of noise. The topographic pattern analysis showed activation of the central-parietal-occipital region of the brain in individuals with ANSD, whereas activation of the central-parietal region was observed in individuals with normal hearing. The activation was more diffused in individuals with ANSD compared with that of individuals with normal hearing. Conclusion The individuals with ANSD showed a significantly more adverse effect of noise on the neural discrimination skill than the normal counterpart.